Legal Principles and their Evolution in Commercial Law - Pérez, Yina Constanza (DIXI, 2017)
Purpose: This essay aims to show how commercial law, as a behavior of man in society, is not alien to legal principles. Description: The fact that this legal branch is relatively new regarding its codification shows that its genesis is as old as man. Therefore, this work demonstrates how the general principles of law have permeated this specialty. Point of view: The research deals with the following legal question: How have the general principles of law permeated commercial law and how has it evolved? It is answered using the method proposed by Tomás Austin, and Frida Gisela Ortiz-Uribe and María del Pilar García. Hernán Valencia-Restrepo, Norberto Bobbio, Ronald Dworkin, among others give the theoretical basis. Conclusions: The commercial sphere must be affected by said trend; otherwise, it would be excluded from the context proposed by this new concept.